2020
DOI: 10.1007/s00394-020-02235-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the satiating properties of medium-chain triglycerides and conjugated linoleic acid in participants with healthy weight and overweight or obesity

Abstract: Purpose Inconsistent evidence exists for greater satiety after medium-chain triglycerides (MCT) or conjugated linoleic acid (CLA) compared to long-chain triglycerides (LCT). Furthermore, the mechanisms are poorly understood and effects in people with a healthy weight and those with overweight/obesity have not been compared. This study aimed to compare appetite responses in these groups and examine the mechanisms behind any differences. Methods Fifteen participants with healthy weight (BMI: 22.7 ± 1.9 kg•m −2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
1
5
0
1
Order By: Relevance
“…It has been reported that the menstrual cycle affects the energy metabolism ( 33 ), and it is possible that the menstrual cycle affects the ketone body production. Maher et al investigated the energy metabolism with women participants to consider the estrous cycle ( 34 ). To accumulate further evidence, it is essential to acquire knowledge about the utilization of the ketogenic formula and to establish a ketogenic diet regimen that can be safely implemented for various individuals, such as women and patients with cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the menstrual cycle affects the energy metabolism ( 33 ), and it is possible that the menstrual cycle affects the ketone body production. Maher et al investigated the energy metabolism with women participants to consider the estrous cycle ( 34 ). To accumulate further evidence, it is essential to acquire knowledge about the utilization of the ketogenic formula and to establish a ketogenic diet regimen that can be safely implemented for various individuals, such as women and patients with cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also reported the production of β‐hydroxybutyrate is responsible for satiation due to glucose sparing action. Although several other mechanisms, such as slower gastric emptying and attenuation of decrease in blood glucose, are also linked to this (Maher et al., 2020). The level of carbohydrate intake may also play a role here.…”
Section: Health Benefits Of Mct Oilmentioning
confidence: 99%
“…Maher i wsp. [32] wykazali, że podaż oleju MCT przyczynia się do zwiększenia uczucia sytości i zmniejszenia ilość przyjmowanych kalorii, dzięki zdolności szybkiego wchłaniania oraz produkcji anoreksogennych ciał ketonowych. Opóźnienie opróżniania żołądka oraz zwiększone stężenia β -hydroksymaślanu stanowią elementy mogące przysłużyć się do zwiększonej kontroli przyjmowanych posiłków.…”
Section: Właściwości Prozdrowotneunclassified